2009
DOI: 10.1002/ps.1707
|View full text |Cite
|
Sign up to set email alerts
|

Effect of additives in aqueous formulation on the foliar uptake of dimethomorph by cucumbers

Abstract: Although the foliar uptake of dimethomorph from both aqueous WP suspensions and aqueous acetone solutions was greatest in the presence of fatty alcohol ethoxylates generally having a C(16) or C(18) lipophile, uptake from aqueous surfactant-acetone solutions was, on average, 7.6-fold greater than that from aqueous WP suspensions containing surfactant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…uptake into the plant tissue or phototransformation) were wileyonlinelibrary.com/journal/ps assumed to be negligible. 56,57 If these dissipation mechanisms are not negligible, then PEARL is expected to predict higher values of emission than would occur in practice. However, additional simulations were performed with photodegradation and tissue penetration accounted for.…”
Section: Emission Rate Calculations With a Pesticide Emission Modelmentioning
confidence: 94%
See 1 more Smart Citation
“…uptake into the plant tissue or phototransformation) were wileyonlinelibrary.com/journal/ps assumed to be negligible. 56,57 If these dissipation mechanisms are not negligible, then PEARL is expected to predict higher values of emission than would occur in practice. However, additional simulations were performed with photodegradation and tissue penetration accounted for.…”
Section: Emission Rate Calculations With a Pesticide Emission Modelmentioning
confidence: 94%
“…58,59 For penetration into the plant, a half-life of 5 days was used. 56,57,60,61 An estimated half-life for penetration of 0.5 days was used to simulate intense uptake by the plant. The applied pesticide doses (Table 1) were used as input for PEARL, and the 'plant only' option of PEARL alone was used for computations from a plant canopy 49 because the crops were mature and the crop canopy was fully closed.…”
Section: Emission Rate Calculations With a Pesticide Emission Modelmentioning
confidence: 99%
“…We are defining dislodgeable residues more broadly to represent the proportion of a compound that has not penetrated the plant cuticle sufficiently to resist physical removal from the plant surface. The stability of a material on a particular plant surface is dependent upon its affinity to the cuticle and epicuticular wax, environmental factors, such as temperature, moisture, and drying time, and the form of physical contact causing removal. Studies of pyrethroid and organophosphate insecticides on leaf surfaces have shown that bioavailability of residues varies among plant species, suggesting that, in some cases, there is sufficient sorption into the plant cuticle to modify contact toxicity from surface exposure to the pest. , Buchholz and Nauen compared the translocation and translaminar movement of two neonicotinoid insecticides, imidacloprid and acetamiprid, on cotton and cabbage leaves. Even though the intrinsic toxicity of these two compounds to green peach aphid, Myzus persicae (Sulzer), and cotton aphid, Aphis gossypii (Glover), were equal, differences were found in the ultimate pest efficacy based on the translaminar and acropetal patterns of insecticide movement in each of the two plant types.…”
Section: Introductionmentioning
confidence: 99%
“…The effect on rust efficacy was seen in both the glasshouse and the field environment, an important step when considering the possible effects of differences in cuticle morphology between greenhouse versus field-grown wheat plants, a phenomenon which did not correlate for the parameter affecting formulation drop retention (12). In the literature, adjuvants have been shown to increase biological activity of fungicides due to improved spray deposition and uptake (25,26,27,28,29). These results are consistent with studies with prothioconazole applied as an EC with and without spiroxamine, in which improved uptake into wheat leaves was observed in the presence of spiroxamine and attributed to an adjuvant effect (30).…”
Section: Discussionmentioning
confidence: 99%